Adsorption of Arsenic and Cadmium on Biodegradable and Non-Biodegradable Microplastics in Soil: Comparison Based on Batch Experiment - Zaw Min Han; Sartaj Ahmad Bhat; Shiamita Kusuma Dewi; Yongfen Wei; Fusheng Li (Soil Systems)
In the present study, the adsorption of arsenic(V) and cadmium(II) onto microplastics from poly(butylene succinate-co-butylene adipate) (PBSA) and low-density polyethylene (LDPE) plastic mulch films was investigated through batch experiment. The surface morphology and elemental composition of soil and microplastics were analyzed with scanning electron microscopy equipped with energy-dispersive X-ray spectroscopy (SEM-EDX) and Fourier-transform infrared (FTIR) spectroscopy. The results show that the adsorption of As(V) and Cd(II) on microplastics led to surfaces with coarseness and more cracks, and many small particles. Under the conditions added with 100 pieces of microplastic, PBSA enhanced the adsorption capacity of As(V) (from 0.43 to 0.49 mg/g), and LDPE increased the adsorption of Cd(II) (from 0.174 to 0.176 mg/g) due to the “superimposed effect” caused by hydrogen bonds. Conversely, LDPE reduced the adsorption of As(V) (from 0.44 to 0.40 mg/g) due to a “dilution effect” of PE. Particularly, PBSA exhibited an insignificant effect on the adsorption of Cd(II) in soil during the present study. Overall, our findings provide new insights into the impacts of microplastics on the fate and behavior of heavy metals in the soil system.